Blast performance of a bio-mimetic panel based on the structure of nacre – A numerical study. (15th February 2020) - Ghazlan, Abdallah; Ngo, Tuan; Van Le, Tu; Nguyen, Tuan; Remennikov, Alex
Abstract: Nacre, the tough protective layer of a mollusk seashell, has a fracture toughness that is several orders of magnitude higher than brittle aragonite, a ceramic that accounts for 95% of its composition. As such, it possesses characteristics that may be highly beneficial for protective structural applications. In this research, several structural characteristics from nacre's brick and mortar-like microstructure are mimicked with the goal of enhancing the stiffness and fracture toughness of a monolithic ceramic panel under blast loading. These features include the mineral bridges connecting the adjacent brick-like tablets for enhancing the stiffness of the panel, the multi-layered structure for enhancing its toughness via crack bridging mechanisms and the growth bands between the nacreous tablet layers for deflecting cracks. The results from the numerical simulations showed that the nacre-like panel possesses superior energy dissipation over the monolithic ceramic panel, which thereby reduces the reaction forces transmitted to the supports and mitigates catastrophic failure. This has positive implications in terms of the capability of fine-tuning the structural characteristics of an armor system for defeating impulsive loads, by employing the principles adopted in the microstructure of a natural armor system.